Change or Decay : Russia's Dilemma and the West's Response - Shevt︠s︡ova, Lilii︠a︡, 1951- (Book collections on Project MUSE., 2011)
The world is still coping with the consequences of the collapse of the Soviet Union. Two decades later, the West has yet to adjust to the post-Soviet reality and Russia has not settled on its relationship with the rest of the world. In Change or Decay, two of the most respected scholars on Russia analyze how relations are shifting between Russia and the world. In a series of lively and candid conversations, Lilia Shevtsova and Andrew Wood discuss how the Russia of Putin and Medvedev emerged from the ashes of the Soviet Union and the trajectory of Russia's relations with the We.